ОСОБЛИВОСТІ ПІДГОТОВКИ ВИКЛАДАЧІВ ДО ЗАСТОСУВАННЯ КРЕДИТНО-МОДУЛЬНОЇ СИСТЕМИ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2007)
The article is dedicated to the issue of training teachers of higher educational institutions for application of the credit-module system of instruction. The peculiarities of the credit-module system are analyzed, as well as conditions of its effective realization. The expediency is substantiated of training teachers for application  of the mentioned system, relevant experimental data are given.